2017
DOI: 10.1136/bcr-2016-219054
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral haemorrhage as a clinical manifestation of human ehrlichiosis

Abstract: A 16-year-old young man presented to the emergency room with new-onset generalised tonic-clonic seizures. Examination showed a Glasgow score of 13 and predominantly crural left hemiparesis. Imaging demonstrated a right frontoparietal haemorrhage of non-vascular origin with perilesional oedema. Surgical drainage was carried out, but rebleeding occurred within 24 hours following surgery, and again 1 week after discharge. On reinterrogation and examination, infection was suspected and empirical management with do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, the role of CMHs complicating infections [55][56][57][58], in particular, acute infections, has been poorly explored [34,[59][60][61]. To the best of our knowledge, four clinic reports from PLOS NEGLECTED TROPICAL DISEASES different countries described a total of 11 cases of CMH after acute systemic infections in patients ranging in age from 9 to 71 years [62][63][64][65]. Nine cases in two reports correlated the CMHs with specific pathogen infections, spotted fever (SF) rickettsiosis or ehrlichiosis [65].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of CMHs complicating infections [55][56][57][58], in particular, acute infections, has been poorly explored [34,[59][60][61]. To the best of our knowledge, four clinic reports from PLOS NEGLECTED TROPICAL DISEASES different countries described a total of 11 cases of CMH after acute systemic infections in patients ranging in age from 9 to 71 years [62][63][64][65]. Nine cases in two reports correlated the CMHs with specific pathogen infections, spotted fever (SF) rickettsiosis or ehrlichiosis [65].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, four clinic reports from different countries described a total of 11 cases of CMH after acute systemic infections in patients ranging in age from 9 to 71 years[ 62 65 ]. Nine cases in two reports correlated the CMHs with specific pathogen infections, spotted fever (SF) rickettsiosis or ehrlichiosis[ 65 ]. Taken together, this information suggests there are potentially more undiscovered cases of CMHs accompanying acute systemic infections.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study suggested that CME is the leading TBD of dogs in the Philippines [ 7 ]. Aside from causing significant morbidities and fatalities in dogs, E. canis is recognized as a potential zoonotic pathogen after being reported in some cases in humans [ 22 , 23 , 24 ]. Early diagnosis is crucial to control the progress of infection promptly.…”
Section: Discussionmentioning
confidence: 99%
“…Nine cases in two reports correlated the CMHs with specific pathogen infections, spotted fever (SF) rickettsiosis or ehrlichiosis [37]. Taken together, this information suggests there are potentially more undiscovered cases of CMHs accompanying acute systemic infections.…”
Section: Introductionmentioning
confidence: 91%
“…To the best of our knowledge, four clinic reports from different countries described a total of 11 cases of CMH after acute systemic infections in patients ranging in age from 9 to 71 years [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%